Development of Qur'an Tahfidz Learning Model in High School ABBS ( Abidin Billingual Boarding School) Surakarta - Kurniadi, Fajri; Inayati, Nurul Latifatul (ISTAWA, 2024)
One of the best programs offered by SMA ABBS Surakarta is the Tahfidz Class Program (TCP). Through the application of a learning model, the program has produced a number of exceptional hafidz and hafidzah who can complete 10 juz in three years or even more than 30 juz. The purpose of this study is to determine the Tahsin and Tahfidz Al-Qur'an learning model at ABBS Surakarta High School, as well as the procedures for putting these learning methods into practice there. It also intends to examine the approaches and strategies utilized for Al-Qur'an tahfidz learning at ABBS High School Surakarta and to highlight the benefits and drawbacks of the tahfidz learning model at SMA ABBS Surakarta. This study employed a descriptive methodology with a qualitative focus. through gathering information through documentation studies, interviews, and observational methods. The learning model used at SMA ABBS Surakarta is a direct learning model (Direct Instruction), which is based on the research findings. Students learn by step through a process approach, and if they apply this learning model to their studies, they will become more adept at mastering the subjectConsidering that the goal of this process approach is to have students actively develop their potential in order to achieve learning objectives. The learning approach is to ascertain the degree of the ziyadah program (bil-gaib) and the pre-memorization program (bin-nadhr). Bi al-ghaib is the memorization stage, while bin-nadr is the stage that focuses on enhancing Al-Qur'anic reading. The Tahsin, Ziyadah, Murajaah, Tadabur verse, and Dauroh procedures are employed.